Study of the Inhibitive Action of Bakery Waste for Corrosion of Mild Steel in Acid Medium - Rajalakshmi, R.; Subhashini, S.; Leelavathi, S.; Geethanjali, R. (Journal of Nepal Chemical Society, 2010)
Bakery waste-egg shell extract was tested for its inhibitory effect towards mild steel in 0.5 M H2SO4 solution. The corrosion behavior of the egg shell extract on mild steel (MS) was investigated using weight loss experiments, polarization and impedance measurements. It was found that the egg shell extract has good inhibitive action, showing 97.8% efficiency. Inhibition efficiency increased with increasing concentrations of the egg shell extract. Temperature studies were conducted to evaluate the kinetic and thermodynamic parameters. The corrosion inhibition takes place via monolayer type of adsorption on MS surface. Experimental results are fitted into various adsorption isotherms. Tafel polarization studies revealed the mixed mode of inhibition of the egg shell extract. Electrochemical impedance results also confirmed the inhibitive nature of the egg shell extract. The results obtained showed that the extract of the egg shell could serve as an effective, zero cost, environmentally friendly inhibitor for the corrosion of mild steel in sulphuric acid medium. Keywords: Egg shell, corrosion, inhibition, mild steel, H2SO4 solution DOI: 10.3126/jncs.v25i0.3282 Journal of Nepal Chemical Society Volume 25, 2010 pp 29-36